Analisis Kinerja Layanan Fraud Detecting System di Perusahaan Konsultan Keamanan Informasi - Muhammad Raihan Alfikri; S. Sukartini; F. Ferdawati (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
This research aims to find out in depth about the performance of Fraud Detecting System services in information security consulting companies to prevent financial fraud. The research took a qualitative method, in which direct interviews were conducted related to the object under study. Assumed on the action of the experience handled directly by the relevant division which of course can be proven scientifically. The results of the study concluded that PT ITSEC Asia Tbk has a fraud detection strategy through a managed system, namely the Fraud Management System which is able to detect, analyze and monitor fraud risks effectively and complexly. However, the company certainly also faces a variety of major challenges, including regulatory constraints in various regional countries of the ITSEC Asia office, as well as the challenge of the growing threat of fraud. Financial and audit assessments show that PT ITSEC Asia Tbk has implemented rigorous internal and external controls, supported by employee training that enhances fraud awareness and skills. In addition, the company has implemented various technologies and systems to detect and prevent fraud, such as the Cyber Fraud Fusion Center, and has complied with various international standards, including ISO 27001 and Financial Services Authority (OJK) regulations. Overall, PT ITSEC Asia Tbk continues to innovate and adapt to technological changes to protect clients' businesses from all cyber threats to ensure their business continuity